The current state of obesity solutions in the United States : workshop summary - Olson, Steve, 1956- (Online access: NCBI NCBI Bookshelf., 2014)
"The Current State of Obesity Solutions in the United States is the summary of a workshop convened in January 2014 by the Institute of Medicine Roundtable on Obesity Solutions to foster an ongoing dialogue on critical and emerging implementation, policy, and research issues to accelerate progress in obesity prevention and care. Representatives of public health, health care, government, the food industry, education, philanthropy, the nonprofit sector, and academia met to discuss interventions designed to prevent and treat obesity. The workshop focused on early care and education, schools, worksites, health care institutions, communities and states, the federal government, and business and industry. For each of these groups, this report provides an overview of current efforts to improve nutrition, increase physical activity, and reduce disparities among populations"--Publisher's description